Depletion attraction in colloidal and bacterial systems - Zhang, Hong; Kong, Dongyang; Zhang, Wenchao; Liu, Huaqing (Frontiers in Materials, 2023)
Depletion attraction is a common entropy force observed in colloidal systems. As a common phenomenon in colloidal and bacterial systems, studying the mechanism and application of depletion attraction is of great value for controlling the state of colloidal solutions, regulating the morphology of colloidal particles, disease treatment, and water pollution treatment. Based on the current research status, we briefly introduce the calculation and measurement methods of depletion attraction. And we review the application of depletion attraction in colloidal systems, and summarize the different phenomena and aggregation mechanisms caused by depletion attraction in active colloidal particlebacterial systems. Understanding the specific role of depletion aggregation in colloidal and bacterial systems provides more possibilities for further exploring depletion aggregation mechanisms and utilizing depletion aggregation phenomena in nature.